Sandwich-structure polymer-based solid electrolyte as well as preparation method and application thereof

By adding high content inorganic filler to the intermediate layer of solid electrolyte and adding low content inorganic filler to both sides of solid electrolyte, the problem that solid electrolyte cannot meet the thickness, flexibility, mechanical properties and conductivity at the same time is solved, and the problem of solid electrolyte cannot be met at the same time, achieving Solid-state electrolyte with high mechanical properties, improved interface contact and cycling properties.

CN119481239AActive Publication Date: 2025-02-18ZHONGTIAN ENERGY STORAGE TECH +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411614689.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The existing solid-state electrolytes are difficult to control thickness, flexibility, mechanical properties and conductivity cannot meet the needs at the same time, which affects the interface contact and cycle life of solid-state batteries.

Method used

The sandwich structure polymer-based solid electrolyte is used to enhance the mechanical properties by adding more inorganic fillers to the intermediate layer; add less inorganic fillers to both sides to improve interface contact; use inorganic fillers of different particle sizes to fill gaps to reduce Lithium dendrites puncture probability.

Benefits of technology

It achieves high mechanical properties, improves interface contact and circulation performance, controllable thickness, low thermal shrinkage, and high ionic conductivity, effectively solving the lithium dendrites problem.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481239A_ABST
    Figure CN119481239A_ABST
Patent Text Reader

Abstract

The invention provides a sandwich-structure polymer-based solid electrolyte and a preparation method and application thereof. The sandwich-structure polymer-based solid electrolyte comprises a first solid electrolyte layer, a second solid electrolyte layer and a third solid electrolyte layer located between the first solid electrolyte layer and the second solid electrolyte layer, the content of the inorganic filler in the third solid electrolyte layer is higher than the content of the inorganic filler in the first solid electrolyte layer; the content of the inorganic filler in the third solid electrolyte layer is higher than the content of the inorganic filler in the second solid electrolyte layer; the inorganic filler in the third solid electrolyte layer comprises a first inorganic filler and a second inorganic filler, and the particle size of the first inorganic filler is smaller than that of the second inorganic filler. According to the preparation method, the mechanical property is favorably improved, the lithium dendrite problem is effectively improved, and the cycle performance and the interface problem are favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a sandwich structure polymer-based solid electrolyte and a preparation method and application thereof, belonging to the technical field of solid electrolytes. Background Art

[0002] Recently, the quality and safety issues in the new energy industry have become prominent. For example, South Korea's energy storage power stations have caught fire and exploded many times, causing South Korea's energy storage industry to stagnate and reorganize many times; the United States' energy storage power stations have also caught fire, causing a huge impact on American society and industry. 80% of the components in liquid electrolytes are flammable organic solvents, which can easily bring serious safety hazards to batteries (such as lithium-ion batteries). Solid-state batteries do not have free electrolytes, and they show great advantages and potential in safety performance. They are the only way for battery development.

[0003] The core of solid-state batteries is solid electrolytes. Among solid-state electrolytes, polymer solid electrolytes and oxide solid electrolytes have the advantages of good flexibility, excellent interface contact and high ionic conductivity, respectively, and have good application prospects. However, the conductivity of polymer solid electrolytes is low and the oxide solid electrolytes are fragile, which limits the application of the two solid electrolytes. The preparation of composite solid electrolytes by combining polymer solid electrolytes and oxide solid electrolytes has become a new direction in the research of solid-state electrolytes. However, this composite solid electrolyte still has the problem of difficult to control thickness, and the flexibility, mechanical properties and conductivity of the single-layer polymer / oxide composite solid electrolyte cannot meet the requirements at the same time, which further affects the electrical properties of solid-state batteries such as interface contact and cycle life.

[0004] Therefore, it is urgent to develop a solid electrolyte that can help improve performance such as interface contact and cycle life. Summary of the invention

[0005] The present invention provides a sandwich structure polymer-based solid electrolyte and a preparation method and application thereof, which has high mechanical properties, effectively improves the lithium dendrite problem, and helps to improve cycle performance and interface problems.

[0006] The present invention provides a sandwich structure polymer-based solid electrolyte, comprising a first solid electrolyte layer, a second solid electrolyte layer, and a third solid electrolyte layer located between the first solid electrolyte layer and the second solid electrolyte layer; the content of the inorganic filler in the third solid electrolyte layer is higher than the content of the inorganic filler in the first solid electrolyte layer; the content of the inorganic filler in the third solid electrolyte layer is higher than the content of the inorganic filler in the second solid electrolyte layer; the inorganic filler in the third solid electrolyte layer comprises a first inorganic filler and a second inorganic filler, and the particle size of the first inorganic filler is smaller than the particle size of the second inorganic filler.

[0007] Optionally, the ratio of the particle size of the first inorganic filler to the particle size of the second inorganic filler is 1:(1-1000), and the ratio of the particle size of the first inorganic filler to the particle size of the second inorganic filler is not 1.

[0008] Optionally, the particle size of the first inorganic filler is 10-500 nm, and the particle size of the second inorganic filler is 1-10 μm.

[0009] Optionally, the mass ratio of the first inorganic filler to the second inorganic filler is (1-2):(2-10).

[0010] Optionally, the first solid electrolyte layer comprises, by mass percentage, 40% to 100% of a first polymer, 0% to 60% of the inorganic filler, and 1% to 10% of a first lithium salt; the second solid electrolyte layer comprises, by mass percentage, 40% to 100% of a third polymer, 0% to 60% of the inorganic filler, and 1% to 10% of a third lithium salt; the third solid electrolyte layer comprises, by mass percentage, 25% to 100% of a second polymer, 0% to 75% of the inorganic filler, and 1% to 10% of a second lithium salt.

[0011] Optionally, the inorganic filler includes one or more of lithium aluminum titanium phosphorus oxide, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium lanthanum zirconium titanium oxide, aluminum oxide, silicon oxide, hafnium oxide, and barium titanate; and / or, the first inorganic filler and the second inorganic filler each independently include one or more of aluminum oxide, silicon oxide, hafnium oxide, and barium titanate.

[0012] The present invention also provides a method for preparing the sandwich structure polymer-based solid electrolyte as described above, comprising: mixing a first polymer, an inorganic filler, a first lithium salt and a first solvent, and obtaining a first solid electrolyte slurry after a first grinding; coating the first solid electrolyte slurry on a substrate, and obtaining a first solid electrolyte layer after a first drying; mixing a second polymer, an inorganic filler, a second lithium salt and a second solvent, and obtaining a second solid electrolyte slurry after a second grinding; coating the second solid electrolyte slurry on a substrate, and obtaining a second solid electrolyte layer after a second drying; coating a third polymer, the first inorganic filler, the second inorganic filler, a third lithium salt and a third solvent; The invention relates to a method for preparing a polymer-based solid electrolyte layer comprising: mixing the first solid electrolyte layer and the second solid electrolyte layer to obtain a third solid electrolyte slurry; coating the third solid electrolyte slurry on a substrate, and obtaining the third solid electrolyte layer after a third drying; the sum of the addition amounts of the first inorganic filler and the second inorganic filler is higher than the addition amount of the inorganic filler in the first solid electrolyte layer, and the sum of the addition amounts of the first inorganic filler and the second inorganic filler is higher than the addition amount of the inorganic filler in the second solid electrolyte layer; stacking the first solid electrolyte layer, the third solid electrolyte layer, and the second solid electrolyte layer in sequence, and pressing them at 80-120 MPa and 160-200° C. to obtain the sandwich structure polymer-based solid electrolyte.

[0013] Optionally, during the first grinding process, the grinding is first performed at a rotation speed of 80 to 120 rpm for 8 to 12 min, then at a rotation speed of 480 to 520 rpm for 18 to 22 min, and finally at a rotation speed of 780 to 820 rpm for 38 to 42 min; and / or, the first solid electrolyte slurry is coated on the substrate, and after the first drying, the process of obtaining the first solid electrolyte layer includes: after removing bubbles from the first solid electrolyte slurry, 8 to 12 mL of the first solid electrolyte slurry after removing bubbles is coated on a plane area of ​​380 to 420 cm 2 The first solid electrolyte layer is obtained after the first drying at 58-62° C. on the substrate; and / or, during the second grinding process, the first grinding is performed at a rotation speed of 80-120 rpm for 8-12 min, then at a rotation speed of 480-520 rpm for 18-22 min, and finally at a rotation speed of 780-820 rpm for 38-42 min; and / or, the second solid electrolyte slurry is coated on the substrate, and after the second drying, the second solid electrolyte layer is obtained. The process includes: after removing bubbles in the second solid electrolyte slurry, 8-12 mL of the second solid electrolyte slurry after removing bubbles is coated on a plane area of ​​380-420 cm 2The second solid electrolyte layer is obtained after the second drying at 58-62° C. on the substrate; and / or the third solid electrolyte slurry is coated on the substrate, and after the third drying, the third solid electrolyte layer is obtained. The process comprises: removing bubbles from the third solid electrolyte slurry, coating 8-12 mL of the third solid electrolyte slurry after removing bubbles on a plane area of ​​380-420 cm 2 After a second drying at 58-62° C. on the substrate, the third solid electrolyte layer is obtained.

[0014] Optionally, the first polymer, the second polymer, and the third polymer each independently include one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene terpolymer, and polyvinylidene fluoride-trifluoroethylene copolymer; and / or, the first lithium salt, the second lithium salt, and the third lithium salt each independently include one or more of lithium bis(trifluoromethanesulfonyl)imide and lithium hexafluorophosphate.

[0015] The present invention also provides a solid-state battery, comprising the sandwich structure polymer-based solid electrolyte as described above or the sandwich structure polymer-based solid electrolyte obtained according to the preparation method as described above.

[0016] The present invention provides a sandwich structure polymer-based solid electrolyte and a preparation method and application thereof, which have high mechanical properties and high density, effectively improving the lithium dendrite problem, and have controllable thickness, low thermal shrinkage, high ionic conductivity, effectively solving interface problems, and improving cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is the discharge energy retention rate curve of the solid-state battery of Example 1;

[0018] Figure 2 is the discharge energy retention rate curve of the solid-state battery of Example 2;

[0019] Figure 3 is the discharge energy retention rate curve of the solid-state battery of Example 3;

[0020] Figure 4 : is the discharge energy retention rate curve of the solid-state battery of Comparative Example 1;

[0021] Figure 5 : is the discharge energy retention rate curve of the solid-state battery of comparative example 2;

[0022] Figure 6 3 is the discharge energy retention rate curve of the solid-state battery of Comparative Example 3;

[0023] Figure 7 Schematic diagram of the structure of a sandwich structure polymer-based solid electrolyte in some embodiments. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] An embodiment of the present invention provides a sandwich structure polymer-based solid electrolyte, comprising a first solid electrolyte layer, a second solid electrolyte layer, and a third solid electrolyte layer located between the first solid electrolyte layer and the second solid electrolyte layer; the content of the inorganic filler in the third solid electrolyte layer is higher than the content of the inorganic filler in the first solid electrolyte layer; the content of the inorganic filler in the third solid electrolyte layer is higher than the content of the inorganic filler in the second solid electrolyte layer; the inorganic filler in the third solid electrolyte layer comprises a first inorganic filler and a second inorganic filler, and the particle size of the first inorganic filler is smaller than the particle size of the second inorganic filler.

[0026] According to the inventor's research and analysis: the third solid electrolyte layer of the sandwich structure polymer-based solid electrolyte contains more inorganic fillers, that is, the middle solid electrolyte layer contains more inorganic fillers, which helps to enhance the mechanical properties of the sandwich structure polymer-based solid electrolyte and inhibit lithium dendrites from piercing the electrolyte, while the first solid electrolyte layer and the second solid electrolyte layer contain less inorganic fillers, that is, the solid electrolyte layers on both sides contain less inorganic fillers, which helps to improve the interface contact problem between the solid electrolyte and the positive and negative electrodes; in addition, the third solid electrolyte layer (middle layer) includes two inorganic fillers with different particle sizes (first filler and second filler), and the inorganic filler with a small particle size can fill the gap of the inorganic filler with a large particle size, reducing the probability of lithium dendrites piercing from the gap, and can further enhance the mechanical properties of the solid electrolyte, prevent lithium dendrites from penetrating the solid electrolyte, thereby preventing short circuits and improving cycle performance.

[0027] Therefore, the sandwich structure polymer-based solid electrolyte provided by the embodiment of the present invention has high mechanical properties, which effectively improves the lithium dendrite problem and helps to improve the cycle performance and interface problems.

[0028] The ratio of the particle size of the first inorganic filler to the particle size of the second inorganic filler may be 1:(1-1000), and the ratio of the particle size of the first inorganic filler to the particle size of the second inorganic filler is not 1.

[0029] Furthermore, the particle size ratio of the first filler to the second filler can be (1-50): (100-1000), for example 1:100, 10:200, 15:400, 20:500:40:700, 1:1000. The inorganic filler with a small particle size can better fill the gaps of the inorganic filler with a large particle size, reduce the probability of lithium dendrites piercing through the gaps, and further enhance the mechanical properties of the solid electrolyte, prevent lithium dendrites from penetrating the solid electrolyte, thereby preventing short circuits and improving cycle performance.

[0030] In some embodiments, the particle size of the first inorganic filler is 10 to 500 nm, for example, 10 nm, 20 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm or a range consisting of any two thereof, and the particle size of the second inorganic filler is 1 to 10 μm, for example, 1 μm, 5 μm, 8 μm, 10 μm or a range consisting of any two thereof. The inorganic filler with a small particle size can better fill the gaps of the inorganic filler with a large particle size, reduce the probability of lithium dendrites piercing through the gaps, and further enhance the mechanics of the solid electrolyte, prevent lithium dendrites from penetrating the solid electrolyte, thereby preventing short circuits and improving cycle performance.

[0031] The mass ratio of the first inorganic filler to the second inorganic filler can be (1-2): (2-10), for example, 1:1, 1:2, 1:5, 1:10 or a range composed of any two of them. The inorganic filler with a small particle size can better fill the gaps of the inorganic filler with a large particle size, reduce the probability of lithium dendrites piercing through the gaps, and further enhance the mechanics of the solid electrolyte, prevent lithium dendrites from penetrating the solid electrolyte, thereby preventing short circuits and improving cycle performance.

[0032] In some embodiments, the first solid electrolyte layer includes, by mass percentage, 40% to 100% of a first polymer, 0% to 60% of an inorganic filler, and 1% to 10% of a first lithium salt.

[0033] The above-mentioned first polymer may include one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene terpolymer (P(VDF-TrFE-CTFE)), and polyvinylidene fluoride-trifluoroethylene copolymer (P(VDF-TrFE)). In specific implementation, a polymer that is the same as the binder in the electrode plate (such as the positive electrode plate) can be selected to help improve the interface contact problem and improve the ionic conductivity. Among them, P(VDF-TrFE-CTFE) has a high dielectric constant, provides a lithium ion percolation channel, improves ionic conductivity, and has strong mechanical properties, inhibits lithium dendrite puncture, and helps improve cycle performance.

[0034] The inorganic filler in the first solid electrolyte layer is hereinafter referred to as the third inorganic filler, and the third inorganic filler may include one or more of lithium aluminum titanium phosphorus oxide (LATP), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanium oxide (LLTO), and lithium lanthanum zirconium titanium oxide (LLZTO).

[0035] The first lithium salt may include one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium hexafluorophosphate.

[0036] Furthermore, in the first lithium salt, the mass ratio of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to lithium hexafluorophosphate may be 10:(3-4), for example, 10:3, 10:3.2, 10:3.5, 10:4 or a range of any two thereof.

[0037] In some embodiments, the second solid electrolyte layer includes, by weight percentage, 40% to 100% of a second polymer, 0% to 60% of an inorganic filler, and 1% to 10% of a second lithium salt.

[0038] The above-mentioned second polymer may include one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene terpolymer (P(VDF-TrFE-CTFE)), and polyvinylidene fluoride-trifluoroethylene copolymer (P(VDF-TrFE)). In specific implementation, a polymer that combines well with the electrode plate (such as the negative electrode plate) can be selected to help improve the interface contact problem and improve the ion conductivity. Among them, P(VDF-TrFE-CTFE) has a high dielectric constant, provides a lithium ion percolation channel, improves ion conductivity, and has strong mechanical properties, inhibits lithium dendrite puncture, and helps improve cycle performance.

[0039] The inorganic filler in the second solid electrolyte layer is hereinafter referred to as a fourth inorganic filler, and the fourth inorganic filler may include one or more of aluminum oxide, silicon oxide, and hafnium oxide.

[0040] The second lithium salt may include one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium hexafluorophosphate.

[0041] Furthermore, in the second lithium salt, the mass ratio of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to lithium hexafluorophosphate may be 10:(3-4), for example, 10:3, 10:3.2, 10:3.5, 10:4 or a range of any two thereof.

[0042] In some embodiments, the third solid electrolyte layer includes, by mass percentage, 25% to 100% of a third polymer, 0% to 75% of an inorganic filler (including a first inorganic filler and a second inorganic filler), and 1% to 10% of a third lithium salt.

[0043] The third polymer may include one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene terpolymer (P(VDF-TrFE-CTFE)), and polyvinylidene fluoride-trifluoroethylene copolymer (P(VDF-TrFE)). Among them, P(VDF-TrFE-CTFE) has a high dielectric constant, provides a lithium ion percolation channel, improves ion conductivity, and has strong mechanical properties, inhibits lithium dendrite puncture, and helps improve cycle performance.

[0044] The first inorganic filler and the second inorganic filler each independently include one or more of aluminum oxide (Al2O3), silicon oxide, and hafnium oxide.

[0045] The third lithium salt may include one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium hexafluorophosphate.

[0046] Furthermore, in the second lithium salt, the mass ratio of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to lithium hexafluorophosphate may be 10:(3-4), for example, 10:3, 10:3.2, 10:3.5, 10:4 or a range of any two thereof.

[0047] Figure 7 Schematic diagram of the structure of a sandwich structure polymer-based solid electrolyte in some embodiments.

[0048] The embodiment of the present invention also provides a method for preparing the above-mentioned sandwich structure polymer-based solid electrolyte, comprising: mixing a first polymer, an inorganic filler, a first lithium salt and a first solvent, and obtaining a first solid electrolyte slurry after a first grinding; coating the first solid electrolyte slurry on a substrate, and obtaining a first solid electrolyte layer after a first drying; mixing a second polymer, an inorganic filler, a second lithium salt and a second solvent, and obtaining a second solid electrolyte slurry after a second grinding; coating the second solid electrolyte slurry on a substrate, and obtaining a second solid electrolyte layer after a second drying; coating a third polymer, a first inorganic filler, a second inorganic filler, The third lithium salt and the third solvent are mixed to obtain a third solid electrolyte slurry; the third solid electrolyte slurry is coated on the substrate, and after a third drying, a third solid electrolyte layer is obtained; the sum of the addition amounts of the first inorganic filler and the second inorganic filler is higher than the addition amount of the inorganic filler in the first solid electrolyte layer, and the sum of the addition amounts of the first inorganic filler and the second inorganic filler is higher than the addition amount of the inorganic filler in the second solid electrolyte layer; the first solid electrolyte layer, the third solid electrolyte layer, and the second solid electrolyte layer are stacked in sequence, and pressed at 80-120 MPa and 160-200° C. to obtain a sandwich structure polymer-based solid electrolyte.

[0049] According to the inventor's research and analysis: adding more inorganic fillers to the third solid electrolyte layer (middle layer) of the sandwich structure polymer-based solid electrolyte can help enhance the mechanical properties of the sandwich structure polymer-based solid electrolyte and inhibit lithium dendrites from piercing the electrolyte, while adding less inorganic fillers to the first solid electrolyte layer and the second solid electrolyte layer (two side layers), that is, the solid electrolyte layers on both sides contain less inorganic fillers, which helps to improve the interface contact problem between the solid electrolyte and the positive and negative electrodes and improve the ionic conductivity; the third solid electrolyte layer (middle layer) includes two inorganic fillers with different particle sizes (first filler and second filler), and the inorganic filler with a small particle size can fill the gap of the inorganic filler with a large particle size, thereby reducing the probability of lithium dendrites piercing through the gap, and can also The mechanical properties of the solid electrolyte are further enhanced, lithium dendrites are prevented from penetrating the solid electrolyte, thereby preventing short circuits and improving cycle performance (cycle life). In addition, the preparation method obtains three electrolyte layers by coating (solution casting or pouring), and then stacks and presses the three electrolyte layers (folding and hot pressing). By adjusting the coating amount and the content of the polymer (organic polymer) and inorganic filler, a sandwich structure polymer-based solid electrolyte (organic-inorganic hybrid polymer electrolyte or film) with a thickness of 5 to 50 μm can be obtained, which is convenient for adjusting the thickness of the sandwich structure polymer-based solid electrolyte and further reducing the thickness of the sandwich structure polymer-based solid electrolyte, thereby simultaneously solving the problem of the difficulty in controlling the thickness of the solid electrolyte and the interface problem.

[0050] In some embodiments, the first solvent includes N-methylpyrrolidone and / or dimethylformamide (DMF) or dimethylacetamide (DMAc).

[0051] In some embodiments, during the first grinding process, the rotation speed is 80-120 rpm, such as 80 rpm, 90 rpm, 100 rpm, 110 rpm, 120 rpm or any two thereof, and the grinding time is 8-12 min, such as 8 min, 9 min, 10 min, 11 min, 12 min or any two thereof. Then, the rotation speed is 480-520 rpm, such as 480 rpm, 490 rpm, 500 rpm, 510 rpm, 520 rpm or any two thereof, and the grinding time is 18-22 min, such as 18 min, 19 min, 20 min, 21 min. in, 22min or a range consisting of any two thereof, and finally grinding at a rotation speed of 780-820rpm, such as 780rpm, 790rpm, 800rpm, 810rpm, 820rpm or a range consisting of any two thereof, for 38-42min, such as 38min, 39min, 40min, 41min, 42min or a range consisting of any two thereof. Grinding at a lower rotation speed first helps to disperse the material, and then grinding at a higher rotation speed further refines the material to obtain a viscous first solid electrolyte slurry, which helps to improve the mechanical properties of the sandwich structure polymer-based solid electrolyte, improve interface problems and cycle performance.

[0052] In specific implementation, the weighed first polymer, inorganic filler (called the third inorganic filler), and first lithium salt can be added to a ball mill, and then a certain volume of the first solvent can be taken by a pipette and added to the ball mill for the above-mentioned first grinding to obtain the first solid electrolyte slurry.

[0053] The energy density of most solid electrolytes is lower than expected, which is mainly due to the excessive thickness and weight of the solid electrolytes. The existing preparation methods of polymer electrolytes are mainly casting film and coating methods. However, these two methods are difficult to accurately control the thickness of the polymer electrolyte (membrane). The thickness of some polymer electrolytes is too low and the mechanical properties are poor, which leads to lithium dendrite piercing and affects the cycle life of the battery. The thickness of the polymer electrolyte (membrane) is relatively high, which leads to the increase of the shuttle path of lithium ions and a significant decrease in ionic conductivity, resulting in the inability to circulate the battery at room temperature, and also increases the weight and cost of the battery.

[0054] In some embodiments, the first solid electrolyte slurry is coated on the substrate, and after the first drying, the process of obtaining the first solid electrolyte layer includes: removing bubbles in the first solid electrolyte slurry, coating 8 to 12 mL of the first solid electrolyte slurry after the bubbles are removed on a plane area of ​​380 to 420 cm 2 After the first drying at 58-62° C., a first solid electrolyte layer is obtained. For example, the volume of the first solid electrolyte slurry after the bubbles are removed may be 8 mL, 9 mL, 10 mL, 11 mL, 12 mL, or any two thereof, and the plane area of ​​the substrate may be 380 cm 2 、390cm 2 、400cm 2 、410cm 2 、420cm 2 The first drying temperature can be 58° C., 60° C., 62° C., or any two thereof. By adjusting the coating amount, it is helpful to flexibly adjust the thickness of the first solid electrolyte layer, thereby adjusting the sandwich structure polymer-based solid electrolyte.

[0055] In specific implementation, the first solid electrolyte slurry can be filtered at least twice using a vacuum filter, and the time for each filtration can be 20±5 minutes to remove bubbles in the first solid electrolyte slurry. Then a certain volume of the first solid electrolyte slurry after the bubbles are removed can be measured using a measuring cylinder (or sucked with a rubber-tipped dropper), and poured onto the substrate. After the first solid electrolyte slurry automatically extends to the entire substrate, it is placed in a vacuum oven for a first drying to obtain a first solid electrolyte layer.

[0056] In some embodiments, the second solvent includes N-methylpyrrolidone and / or dimethylformamide, dimethylacetamide (DMAc).

[0057] In some embodiments, during the second grinding process, the grinding may be performed at a rotation speed of 80 to 120 rpm, such as 80 rpm, 90 rpm, 100 rpm, 110 rpm, 120 rpm, or any two thereof, for 8 to 12 min, such as 8 min, 9 min, 10 min, 11 min, 12 min, or any two thereof, and then at a rotation speed of 480 to 520 rpm, such as 480 rpm, 490 rpm, 500 rpm, 510 rpm, 520 rpm, or any two thereof, for 18 to 22 min, such as 18 min, 19 min, 20 min, 21 min. in, 22min or a range consisting of any two thereof, and finally grinding at a rotation speed of 780-820rpm, such as 780rpm, 790rpm, 800rpm, 810rpm, 820rpm or a range consisting of any two thereof, for 38-42min, such as 38min, 39min, 40min, 41min, 42min or a range consisting of any two thereof. Grinding at a lower rotation speed first helps to disperse the material, and then grinding at a higher rotation speed further refines the material to obtain a viscous second solid electrolyte slurry, which helps to improve the mechanical properties of the sandwich structure polymer-based solid electrolyte, improve interface problems and cycle performance.

[0058] In specific implementation, the weighed second polymer, inorganic filler (fourth inorganic filler), and second lithium salt can be added to a ball mill first, and then a certain volume of the second solvent can be taken by a pipette and added to the ball mill for the above-mentioned second grinding to obtain the second solid electrolyte slurry.

[0059] In some embodiments, the second solid electrolyte slurry is coated on the substrate, and after the first drying, the process of obtaining the first solid electrolyte layer includes: removing bubbles in the second solid electrolyte slurry, coating 8 to 12 mL of the second solid electrolyte slurry after the bubbles are removed on a plane area of ​​380 to 420 cm 2 The second solid electrolyte layer is obtained after a second drying at 58-62° C. on a substrate. For example, the volume of the second solid electrolyte slurry after the bubbles are removed may be 8 mL, 9 mL, 10 mL, 11 mL, 12 mL, or any two thereof, and the plane area of ​​the substrate may be 380 cm 2 、390cm 2 、400cm 2 、410cm 2 、420cm 2 The second drying temperature can be 58° C., 60° C., 62° C., or any two thereof. By adjusting the coating amount, it is helpful to flexibly adjust the thickness of the second solid electrolyte layer, thereby adjusting the sandwich structure polymer-based solid electrolyte.

[0060] In specific implementation, the second solid electrolyte slurry can be filtered at least twice using a vacuum filter, and the time for each filtration can be 20±5 minutes to remove bubbles in the second solid electrolyte slurry. Then, a certain volume of the second solid electrolyte slurry after the bubbles are removed can be measured using a measuring cylinder and poured onto the substrate. After the second solid electrolyte slurry automatically extends to the entire substrate, it is placed in a vacuum oven for a second drying to obtain a second solid electrolyte layer.

[0061] In some embodiments, the third solvent includes N-methylpyrrolidone and / or dimethylformamide, dimethylacetamide (DMAc).

[0062] In the process of mixing the third polymer, the first inorganic filler, the second inorganic filler, the third lithium salt and the third solvent to obtain the third solid electrolyte slurry, the mixed material can be stirred to make it uniformly mixed. For example, the mixed material can be placed in a glass bottle and stirred using a constant temperature magnetic stirrer to obtain a viscous third solid electrolyte slurry, wherein the stirring temperature can be 48-52°C, for example, 48°C, 50°C, 52°C or a range composed of any two thereof.

[0063] In some embodiments, the third solid electrolyte slurry is coated on the substrate, and after the third drying, the process of obtaining the third solid electrolyte layer includes: removing bubbles in the third solid electrolyte slurry, coating 8 to 12 mL of the third solid electrolyte slurry after the bubbles are removed on a plane area of ​​380 to 420 cm 2 After a second drying at 58-62° C., a third solid electrolyte layer is obtained. For example, the volume of the third solid electrolyte slurry after the bubbles are removed may be 8 mL, 9 mL, 10 mL, 11 mL, 12 mL, or any two thereof, and the plane area of ​​the substrate may be 380 cm 2 、390cm 2 、400cm 2 、410cm 2 、420cm 2 The temperature of the third drying can be 58° C., 60° C., 62° C., or any two thereof. By adjusting the coating amount, it is helpful to flexibly adjust the thickness of the third solid electrolyte layer, thereby adjusting the sandwich structure polymer-based solid electrolyte.

[0064] In specific implementation, the third solid electrolyte slurry can be filtered at least twice using a vacuum filter, and the time for each filtration can be 20±5 minutes to remove bubbles in the third solid electrolyte slurry. Then, a certain volume of the third solid electrolyte slurry after the bubbles are removed can be measured using a measuring cylinder and poured onto the substrate. After the third solid electrolyte slurry automatically extends to the entire substrate, it is placed in a vacuum oven for a third drying to obtain a third solid electrolyte layer.

[0065] In some embodiments, the substrate comprises a glass plate, such as an ultra-flat glass plate with a length and width of 20±1 cm.

[0066] For example, the pressure of the pressing process may be 80 MPa, 90 MPa, 100 MPa, 110 MPa, 120 MPa or any two thereof, and the temperature of the pressing process may be 160° C., 170° C., 180° C., 190° C., 200° C. or any two thereof, which is helpful to flexibly control the thickness of the sandwich structure polymer-based solid electrolyte.

[0067] In a specific implementation, the first solid electrolyte layer, the third solid electrolyte layer, and the second solid electrolyte layer can be stacked in sequence in a special mold and pressed at 80-120 MPa and 160-200°C for 40-50 min, for example, 40 min, 45 min, 50 min or a range composed of any two thereof, and after cooling, a sandwich structure polymer-based solid electrolyte is obtained.

[0068] The above-mentioned special mold can be made of manganese steel, which has the characteristic of small deformation. The special mold can be divided into three parts: a square base, a square frame, and a square cover. The square cover has a groove, and the height of the groove can be 15 to 50 μm.

[0069] An embodiment of the present invention further provides a solid-state battery, comprising the above-mentioned sandwich structure polymer-based solid electrolyte or the sandwich structure polymer-based solid electrolyte obtained according to the above-mentioned preparation method.

[0070] In specific implementation, the above-mentioned solid-state battery can be a semi-solid-state battery, a quasi-solid-state battery, or an all-solid-state battery, such as a semi-solid-state lithium-ion battery, a semi-solid-state sodium-ion battery, a quasi-solid-state lithium-ion battery, a quasi-solid-state sodium-ion battery, an all-solid-state lithium-ion battery, and an all-solid-state sodium-ion battery.

[0071] It is conceivable that the solid-state battery of the embodiment of the present invention includes a negative electrode sheet and a positive electrode sheet in addition to the above-mentioned sandwich structure polymer-based solid electrolyte.

[0072] The embodiments of the present invention do not strictly limit the negative electrode active material in the negative electrode sheet, and can be at least one of the negative electrode active materials commonly used in lithium-ion batteries, such as graphite, hard carbon, soft carbon, silver-carbon mesophase carbon microspheres, silicon-based negative electrode materials (mainly including silicon oxide, silicon-carbon negative electrode), tin-based negative electrode materials (mainly including tin, tin alloy), etc.

[0073] The embodiments of the present invention do not strictly limit the negative electrode active material in the positive electrode sheet, and may be a positive electrode active material commonly used in current lithium-ion batteries, such as at least one composite oxide of lithium and metals of cobalt, manganese, nickel, and combinations thereof. Specifically, it may be at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganate, lithium manganate, nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium iron phosphate (LFP), lithium nickel manganate, lithium-rich manganese-based material, and the like.

[0074] When preparing a solid-state battery, the positive electrode sheet, the sandwich-structured polymer-based solid electrolyte and the negative electrode sheet are stacked, pressed and packed in an aluminum soft package. A gel electrolyte can be optionally added for in-situ curing to complete the preparation of the solid-state battery.

[0075] The present invention is described in more detail below through specific embodiments.

[0076] Some of the raw materials in the examples are from the following sources:

[0077] Polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene terpolymer (P(VDF-TrFE-CTFE)), polyvinylidene fluoride-trifluoroethylene copolymer (P(VDF-TrFE)): purchased from Aucma.

[0078] Example 1

[0079] This embodiment provides a method for preparing a sandwich structure polymer-based solid electrolyte, comprising:

[0080] 2.5 g P(VDF-TrFE-CTFE), 2.5 g LATP, and 0.25 g LiTFSI were added to a ball mill, 50 mL DMF was measured with a pipette, added to the ball mill, and mixed, and then ball milled at rotation speeds of 100 rpm, 500 rpm, and 800 rpm for 10 min, 20 min, and 40 min, respectively, to obtain a first solid electrolyte slurry; the first solid electrolyte slurry was filtered twice using a vacuum filter, and the filtering time for each time was 20 min to remove bubbles in the first solid electrolyte slurry; 10 mL of the first solid electrolyte slurry after the bubbles were removed was measured with a measuring cylinder and coated on an ultra-flat glass plate with a length and width of 20 cm, and the solution was automatically extended to the entire ultra-flat glass sheet, and then placed in a vacuum oven and dried at 60° C. to obtain a first solid electrolyte layer;

[0081] 2.5 g P(VDF-TrFE-CTFE), 2.5 g Al2O3, and 0.25 g LiTFSI were added to a ball mill, 50 mL DMF was measured with a pipette and added to the ball mill, and then the mixture was ball milled at rotation speeds of 100 rpm, 500 rpm, and 800 rpm for 10 min, 20 min, and 40 min, respectively, to obtain a second solid electrolyte slurry; the second solid electrolyte slurry was filtered twice using a vacuum filter, and each filtration time was 20 min to remove bubbles in the second solid electrolyte slurry; 10 mL of the second solid electrolyte slurry after the bubbles were removed was measured with a measuring cylinder and coated on an ultra-flat glass plate with a length and width of 20 cm, and the solution was automatically extended to the entire ultra-flat glass sheet, and then placed in a vacuum oven and dried at 60° C. to obtain a second solid electrolyte layer;

[0082] 2.5 g P(VDF-TrFE-CTFE), 2.5 g Al2O3 with a particle size of 300 nm, 2.5 g Al2O3 with a particle size of 5000 nm, and 0.25 g LiTFSI were added to a glass bottle, 50 mL of DMF was measured with a pipette and added to the glass bottle for mixing, and then magnetically stirred at a constant temperature of 50° C. to obtain a third solid electrolyte slurry; the third solid electrolyte slurry was filtered twice using a vacuum filter, and the filtering time for each time was 20 min to remove bubbles in the second solid electrolyte slurry; 10 mL of the second solid electrolyte slurry after the bubbles were removed was measured with a measuring cylinder and coated on an ultra-flat glass plate with a length and width of 20 cm, and the solution was automatically extended to the entire ultra-flat glass sheet, and then placed in a vacuum oven and dried at 60° C. to obtain a third solid electrolyte layer;

[0083] The first solid electrolyte layer, the third solid electrolyte layer, and the second solid electrolyte layer were stacked in sequence and pressed at 100 MPa and 180°C for 45 min to obtain a sandwich structure polymer-based solid electrolyte (P(VDF-TrFE-CTFE) / LATP / LiTFSI composite solid electrolyte membrane).

[0084] The sandwich structure polymer-based solid electrolytes of Examples 2 to 3 and Comparative Examples 1 to 3 were prepared by referring to the process of Example 1. Comparative Example 4 is a commercial diaphragm purchased from Shenzhen Xingyuan Material Technology Co., Ltd.

[0085] Parameters such as the types of components in each solid electrolyte layer of each embodiment and comparative example and the mass percentage (content) of each component in each layer are summarized in Table 1.

[0086] Table 1

[0087]

[0088]

[0089] Test Example 1

[0090] 1. The following parameters of the above embodiments and comparative examples were tested:

[0091] 1) Thickness of the sandwich structure polymer-based solid electrolyte and the first solid electrolyte layer, the second solid electrolyte layer, and the third solid electrolyte layer: The thickness of the sandwich structure polymer-based solid electrolyte or the separated first solid electrolyte layer, the second solid electrolyte layer, and the third solid electrolyte layer was measured by using a film thickness meter. The specific results are shown in Tables 2 and 3;

[0092] 2) Needle puncture strength of sandwich structure polymer-based solid electrolyte and the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer: First, cut a sample with a diameter of 100 mm (including the sandwich structure polymer-based solid electrolyte, the first solid electrolyte layer, the second solid electrolyte layer or the third solid electrolyte layer after separation). The sample thickness is uniform and has no wrinkles, folds, stains or other obvious defects. Then, the 90° peel strength test item is selected, with a value of (50±5) mm·min -1 The puncture strength value was obtained by piercing at a speed of 5000 mm / s. Each group of samples includes 5 test pieces, and the arithmetic mean of the 5 test pieces is used to obtain the final test result of the puncture strength. The specific results are shown in Tables 2 and 3.

[0093] 3) Thermal shrinkage of sandwich structure polymer-based solid electrolyte (solid electrolyte): Cut a 10cm×10cm square solid electrolyte sample, lay it flat and sandwich it between two transparent and clean glass plates, then place the glass plate in a blast drying oven that has reached the set temperature and bake it for 1h. After baking, cool the glass plate to room temperature, observe and measure the morphological changes of the square solid electrolyte sample; wherein, the test temperature point (the set temperature of the above-mentioned blast drying oven) is 120°C, and the baking time is 1h; the calculation formula of the thermal shrinkage rate S is: S / %=(S0-S1) / S0×100%, in which S is the thermal shrinkage rate; S0 is the area of ​​the square solid electrolyte sample cut before heat treatment (baking), and S1 is the area of ​​the square solid electrolyte sample after heat treatment (baking), the unit is mm 2 ; Specific results are shown in Table 3;

[0094] 4) Ionic conductivity of sandwich structure polymer-based solid electrolyte and the first solid electrolyte layer, the second solid electrolyte layer, and the third solid electrolyte layer: The ionic conductivity is measured by electrochemical impedance spectroscopy (EIS) and then calculated by the formula. The specific test method is as follows: assemble SS (round stainless steel sheet) / polymer electrolyte / SS blocking battery in the glove box, the test temperature is 25°C, the temperature must be kept constant for more than 2 hours before the test, the test frequency is 1MHz-0.1Hz, and the amplitude voltage is 3mV; use Autolab Rui The test was carried out at the Shiwanhua electrochemical workstation. The measured graph was a semicircle and a straight line with a slope of about 45°. The real impedance of the intersection of the semicircle and the straight line is the bulk resistance Rb of the electrolyte membrane. The ionic conductivity can be calculated by the following formula: σ=L / (Rb*S), where: σ is the ionic conductivity of the test sample (such as a sandwich structure polymer-based solid electrolyte membrane), in S / cm; L is the thickness of the test sample, in cm; Rb is the bulk resistance of the test sample, in Ω; S is the area of ​​the test sample, in cm 2 ; Specific results are shown in Table 2 and Table 3;

[0095] 5) Porosity of the sandwich structure polymer-based solid electrolyte and the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer: The porosity was tested using a surface area analyzer, a US Quantachrome Nova 1200e model device, and nitrogen gas. The specific results are shown in Tables 2 and 3.

[0096] 2. Test results

[0097] Table 2 Thickness, puncture strength, ionic conductivity, and porosity of the first solid electrolyte layer, the second solid electrolyte layer, and the third solid electrolyte layer

[0098]

[0099]

[0100] Table 3 Thickness, ionic conductivity, density and thermal shrinkage of sandwich structure polymer-based solid electrolytes

[0101]

[0102] Data Analysis:

[0103] It can be seen from the analysis of Table 2 and Table 3 that the sandwich structure polymer-based solid electrolyte of the embodiment of the present invention has a higher needle puncture strength and a lower thermal shrinkage rate.

[0104] Test Example 2

[0105] The sandwich-structured polymer-based solid electrolytes and the positive and negative electrode sheets in all the embodiments and comparative examples are stacked, pressed and packed in an aluminum soft package, and gel-state additives are added for in-situ curing to form a solid-state battery, wherein the gel-state additives are purchased from Sinopharm Group. Specifically, the battery core is assembled, including the steps of stacking, packaging, liquid injection and formation, and finally a complete soft-pack battery is formed.

[0106] Among them, the preparation process of the positive electrode sheet and the negative electrode sheet is as follows:

[0107] Preparation of positive electrode sheet: The lithium iron phosphate positive electrode material is mixed evenly with the conductive agent carbon black and the binder polyvinylidene fluoride to form a slurry with good conductivity and adhesion; the prepared slurry is coated on the aluminum foil current collector, usually using a coating machine; the coated aluminum foil is dried to remove the solvent and solidify the solid components in the slurry to obtain a dried positive electrode sheet; the dried positive electrode sheet is compacted by a roller pressing process to increase the volume energy density of the battery to obtain a positive electrode sheet;

[0108] Preparation of negative electrode sheet: The graphite negative electrode material is mixed evenly with the conductive agent carbon black and the binder polyvinylidene fluoride to form a negative electrode slurry; the negative electrode slurry is coated on the copper foil current collector, and after drying and rolling, a negative electrode sheet is obtained.

[0109] The cycle performance of the above solid-state battery was tested:

[0110] The capacity retention rate of each solid-state battery obtained was tested. The specific test method was as follows: place at 45°C for 5 hours, charge to 3.65V at 1P constant power, stand for 15 minutes, then discharge to 2.50V at 1P constant power, stand for 15 minutes, repeat this charge and discharge cycle 500 times, and measure the discharge energy Q1 at the first cycle and the discharge energy Q at the 500th cycle. 500 , the discharge energy retention rate Q after 500 cycles is calculated according to the following formula: capacity retention rate Q = Q 500 / Q1*100%.

[0111] Cycle life: The battery cycle life is evaluated through the capacity decay rate method. The battery is charged and discharged under normal conditions of use. The number of charge and discharge cycles when its capacity drops to 80% or less of the rated capacity is the cycle life. In addition, the battery's decay rate and remaining life are evaluated by calculating the capacity loss rate of the battery in each charge and discharge cycle and drawing a capacity decay curve.

[0112] Table 4 Cycle performance of batteries

[0113]

[0114] Combination Figure 1-Figure 6As shown in Table 4, the sandwich structure polymer-based solid electrolyte provided by the embodiment of the present invention has good cycle stability.

[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A sandwich structure polymer-based solid electrolyte, characterized in that: comprising a first solid electrolyte layer, a second solid electrolyte layer, and a third solid electrolyte layer located between the first solid electrolyte layer and the second solid electrolyte layer; The content of the inorganic filler in the third solid electrolyte layer is higher than the content of the inorganic filler in the first solid electrolyte layer; The content of the inorganic filler in the third solid electrolyte layer is higher than the content of the inorganic filler in the second solid electrolyte layer; The inorganic filler in the third solid electrolyte layer includes a first inorganic filler and a second inorganic filler, and the particle size of the first inorganic filler is smaller than the particle size of the second inorganic filler.

2. The sandwich structure polymer-based solid electrolyte according to claim 1, characterized in that: The ratio of the particle size of the first inorganic filler to the particle size of the second inorganic filler is 1:(1-1000), and the ratio of the particle size of the first inorganic filler to the particle size of the second inorganic filler is not 1.

3. The sandwich structure polymer-based solid electrolyte according to claim 2, characterized in that: The particle size of the first inorganic filler is 10 to 500 nm, and the particle size of the second inorganic filler is 1 to 10 μm.

4. The sandwich structure polymer-based solid electrolyte according to claim 3, characterized in that: The mass ratio of the first inorganic filler to the second inorganic filler is (1-2):(2-10).

5. The sandwich structure polymer-based solid electrolyte according to claim 1, characterized in that: The first solid electrolyte layer comprises, by weight percentage, 40% to 100% of a first polymer, 0% to 60% of an inorganic filler, and 1% to 10% of a first lithium salt; The second solid electrolyte layer comprises, by weight percentage, 40% to 100% of the third polymer, 0% to 60% of the inorganic filler, and 1% to 10% of the third lithium salt; The third solid electrolyte layer comprises, in terms of mass percentage, 25-100% of the second polymer, 0-75% of the inorganic filler, and 1-10% of the second lithium salt.

6. The sandwich structure polymer-based solid electrolyte according to claim 1, characterized in that: The inorganic filler includes one or more of lithium aluminum titanium phosphorus oxide, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium lanthanum zirconium titanium oxide, aluminum oxide, silicon oxide, hafnium oxide, and barium titanate; And / or, the first inorganic filler and the second inorganic filler each independently include one or more of aluminum oxide, silicon oxide, hafnium oxide, and barium titanate.

7. A method for preparing a sandwich structure polymer-based solid electrolyte according to any one of claims 1 to 6, characterized in that: include: Mixing a first polymer, an inorganic filler, a first lithium salt and a first solvent, and obtaining a first solid electrolyte slurry after first grinding; Applying the first solid electrolyte slurry on a substrate, and obtaining a first solid electrolyte layer after first drying; A second polymer, an inorganic filler, a second lithium salt and a second solvent are mixed, and a second solid electrolyte slurry is obtained after a second grinding; the second solid electrolyte slurry is coated on a substrate, and a second drying is performed to obtain a second solid electrolyte layer; A third polymer, the first inorganic filler, the second inorganic filler, a third lithium salt and a third solvent are mixed to obtain a third solid electrolyte slurry; the third solid electrolyte slurry is coated on a substrate, and after a third drying, the third solid electrolyte layer is obtained; the sum of the addition amounts of the first inorganic filler and the second inorganic filler is higher than the addition amount of the inorganic filler in the first solid electrolyte layer, and the sum of the addition amounts of the first inorganic filler and the second inorganic filler is higher than the addition amount of the inorganic filler in the second solid electrolyte layer; The first solid electrolyte layer, the third solid electrolyte layer, and the second solid electrolyte layer are stacked in sequence, and then pressed at 80-120 MPa and 160-200° C. to obtain the sandwich structure polymer-based solid electrolyte.

8. The preparation method according to claim 7, characterized in that: During the first grinding process, the grinding is first performed at a rotation speed of 80 to 120 rpm for 8 to 12 minutes, then at a rotation speed of 480 to 520 rpm for 18 to 22 minutes, and finally at a rotation speed of 780 to 820 rpm for 38 to 42 minutes; And / or, the first solid electrolyte slurry is coated on the substrate, and after the first drying, the process of obtaining the first solid electrolyte layer comprises: after removing bubbles from the first solid electrolyte slurry, coating 8 to 12 mL of the first solid electrolyte slurry after removing bubbles on a surface with a plane area of ​​380 to 420 cm 2 on the substrate, and performing a first drying at 58-62° C. to obtain the first solid electrolyte layer; And / or, during the second grinding process, the grinding is first performed at a rotation speed of 80 to 120 rpm for 8 to 12 min, then at a rotation speed of 480 to 520 rpm for 18 to 22 min, and finally at a rotation speed of 780 to 820 rpm for 38 to 42 min; And / or, the second solid electrolyte slurry is coated on the substrate, and after the second drying, the process of obtaining the second solid electrolyte layer comprises: after removing bubbles from the second solid electrolyte slurry, coating 8 to 12 mL of the second solid electrolyte slurry after removing bubbles on a surface with a plane area of ​​380 to 420 cm 2 on the substrate, and performing a second drying at 58-62° C. to obtain the second solid electrolyte layer; And / or, the third solid electrolyte slurry is coated on the substrate, and after the third drying, the process of obtaining the third solid electrolyte layer comprises: after removing bubbles from the third solid electrolyte slurry, coating 8 to 12 mL of the third solid electrolyte slurry after removing bubbles on a plane area of ​​380 to 420 cm 2 After a second drying at 58-62° C. on the substrate, the third solid electrolyte layer is obtained.

9. The preparation method according to claim 7, characterized in that: The first polymer, the second polymer, and the third polymer each independently include one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene terpolymer, and polyvinylidene fluoride-trifluoroethylene copolymer; And / or, the first lithium salt, the second lithium salt, and the third lithium salt each independently include one or more of lithium bis(trifluoromethanesulfonyl)imide and lithium hexafluorophosphate.

10. A solid-state battery, characterized in that: It comprises the sandwich structure polymer-based solid electrolyte described in any one of claims 1 to 6 or the sandwich structure polymer-based solid electrolyte obtained according to the preparation method described in any one of claims 7 to 9.

Citation Information

Patent Citations

  • Composite solid electrolyte, and preparation method and applications thereof

    CN108598560A

  • All-solid-state electrolyte and preparation method thereof, and lithium ion battery

    CN111180788A

  • Sandwich-structure inorganic solid electrolyte and preparation method and application thereof

    CN117276649A

  • Multilayer composite solid electrolyte sheet or belt and preparation method and application thereof

    CN118248930A

  • Multi-layer composite solid electrolyte for room-temperature solid lithium battery and preparation method of multi-layer composite solid electrolyte

    CN118352607A